Ethylene glycol assisted MnCO3 electrocatalyst for water oxidation and hydrogen production application. (15th October 2021) - Swathi, S.; Yuvakkumar, R.; Senthil Kumar, P.; Ravi, G.; Velauthapillai, Dhayalan; Vo, Dai-Viet N.
Highlights: Rhombohedral phase of MnCO3 nanostructures was determined. MnCO3 @15 ml EG electrode exhibited a small Tafel slope value. MnCO3 @15 ml EG enhanced its catalytic performance. Exhibited high current density 257 mA/g with low 184 mV overpotential. Photocatalytic MnCO3 hydrogen production was explored. Abstract: In this research, manganese carbonate nanostructures were prepared employing simple co-precipitation route using ethylene glycol. Rhombohedral phase of MnCO3 nanostructures was determined by X-ray diffraction. MnCO3 @15 ml EG electrode exhibited small Tafel slope value and significantly facilitating its OER performance. The fabricated electrode materials of MnCO3 nanostructure exhibited high 257 mA/g current density with low 184 mV overpotential. The prepared electrodes explored excellent OER performance and good stability over 16 h without degradation. Organic additive of ethylene glycol tuning its morphology to favor of OER activity and it enhanced the electrochemical performance of MnCO3 nanomaterial. MnCO3 material was also subjected to photocatalytic hydrogen production. There was no activity noticed in the pure water even after 3 h of experiments. The following factor may enhance the H2 evolution rate. They are introducing hetero-atoms in crystal lattice points, combination with carbon materials such as GO, g-C3 N4 etc and composed of heterostructures with some other material such as TMDs, CdS, TiO2 and ZnS etc. Hence, mono metal carbonate of MnCO3 doesn't show any H2 activity and the fabricated electrode was suitable candidate for oxygen evolution reaction.